Imagine going left versus imagine going right: whole-body motion on the lateral axis - K. Patel; J. Stotter; M. C. Pali; I. Giannopulu (Scientific Reports)
Abstract Unlike the conventional, embodied, and embrained whole-body movements in the sagittal forward and vertical axes, movements in the lateral/transversal axis cannot be unequivocally grounded, embodied, or embrained. When considering motor imagery for left and right directions, it is  assumed that participants have underdeveloped representations due to a lack of familiarity with moving along the lateral axis. In the current study, a 32 electroencephalography (EEG) system was used to identify the oscillatory neural signature linked with lateral axis motor imagery. Following the experimental procedure, 36 healthy participants were instructed and trained to imagine moving left and right from a first-person perspective. On average, greater beta oscillatory activity in the parietal region was observed during right motor imagery compared to left motor imagery. Furthermore, lateral whole-body motion imagery is associated with the posterior multimodal somatosensory parietal areas, which showed significantly more prominent cortico-cortical interconnections when performing right than left motor imagery, as indicated by Phase-Locked Value (PLV) analysis. The findings suggest that the mental simulation of lateral movements, reflecting immature neurocognitive schemata, might engender non-grounded and non-embedded somatosensory and kinesthetic representations that would be associated with the lateralisation of the multimodal cortical vestibular network.